Penerapan Metode Pembelajaran Inquiry Dalam Upaya Meningkatkan Motivasi dan Hasil Belajar Pendidikan Agama Islam Pada Kelas XI MIA 3 SMA Negeri 2 Sungguminasa Tahun Pelajaran 2015/2016 - Jawaruddin, Jawaruddin (Universitas Islam Negeri Alauddin Makassar, 2016)
This research was a Classroom Action Research (CAR) which aims to boost students’ motivation and learning achievements on the subjects of Islamic Education at Class XI MIA 3 SMAN 2 Sungguminasa through the implementation of inquiry method. The subjects of this study were all students of Class XI MIA 3 SMAN 2 Sungguminasa. This study was conducted from September to October 2015 by two cycles. The data collecting techniques were in the forms of observation, written test, and documentation. The findings showed that the implementation of inquiry method could improve the motivation and learning achievements of class XI MIA students at 2 SMAN 2 Sungguminasa in academic year 2015/2016. It was supported by the evidence that the students’ motivation increased from the first to the second cycle. Likewise, the students’ learning achievements also increased significantly. In the first cycle, students who had completed were only 58% and the second cycle had reached 82%.